Adaptive Governance of Qur’anic Memorization Curricula in ‎Muslim-Minority Southern Thailand: Integration, Leadership, ‎and Sustainability - Kaluape, Waehamad; Soebahar, Erfan; Fahrurrozi (JPI: Jurnal Pustaka Indonesia, 2025)
Qur’anic memorization (Tahfidz) institutions in Muslim-minority settings must preserve religious identity while meeting national educational expectations, yet limited evidence explains how these demands are governed as an integrated curriculum system. This study analyzes Tahfidz Al-Qur’an curriculum governance at Mahad Al-Bi Sat Al-Diniah Jala and Ma’had Darul Aman Litahfidzil Qur’an Krongpinang Jala in Southern Thailand. Guided by an interpretivist paradigm, the study employed a qualitative multiple-case design involving seven purposively selected leaders, teachers, and a student. Data were generated through approximately 60-minute face-to-face interviews, participant observation, and analysis of curriculum, assessment, scheduling, and administrative documents, then examined through iterative thematic coding and interpretive cross-case synthesis. The findings reveal three interdependent governance mechanisms: integration of Tahfidz, Islamic religious education, and Thailand’s national curriculum through coordinated scheduling and multilingual practice; leadership-driven collaboration supported by clear organizational roles and social capital from parents, alumni, and community actors; and continuous quality assurance through muroja’ah, periodic assessment, progress monitoring, and teacher development. These mechanisms enable the institutions to maintain religious and Patani Malay identity while responding adaptively to teacher shortages, dual-curriculum workload, facility limitations, policy requirements, and social change. The study concludes that effective Tahfidz governance is not merely instructional administration but an adaptive-integrative institutional process linking curricular coherence, relational leadership, cultural-linguistic mediation, stakeholder support, and continuous improvement. The findings imply that faith-based schools in minority contexts require flexible hybrid-curriculum policies, stronger teacher capacity, and institutionalized stakeholder partnerships to sustain both educational quality and cultural legitimacy.